2010
DOI: 10.1209/0295-5075/91/40005
|View full text |Cite
|
Sign up to set email alerts
|

Compass-Heisenberg model on the square lattice —Spin order and elementary excitations

Abstract: PACS 05.30.Rt -Quantum phase transitions PACS 75.10.Jm -Quantized spin models, including quantum spin frustration PACS 03.67.Pp -Quantum error correction and other methods for protection against decoherence Abstract. -We explore the physics of the anisotropic compass model under the influence of perturbing Heisenberg interactions and present the phase diagram with multiple quantum phase transitions. The macroscopic ground state degeneracy of the compass model is lifted in the thermodynamic limit already by inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 29 publications
3
52
0
Order By: Relevance
“…In both these cases the orbital exchange (orbital-flip) processes are blocked and orbital interaction are of a classical Ising-like form. Such Ising interactions are frustrated when they emerge in higher dimension, as in the well-studied orbital compass model [73][74][75] and in Kitaev model [76], see also a recent review on the compass model [77]. It is now intriguing to ask what happens to the SOE in this case.…”
Section: Ising Orbital Interactions (∆ = 0)mentioning
confidence: 99%
“…In both these cases the orbital exchange (orbital-flip) processes are blocked and orbital interaction are of a classical Ising-like form. Such Ising interactions are frustrated when they emerge in higher dimension, as in the well-studied orbital compass model [73][74][75] and in Kitaev model [76], see also a recent review on the compass model [77]. It is now intriguing to ask what happens to the SOE in this case.…”
Section: Ising Orbital Interactions (∆ = 0)mentioning
confidence: 99%
“…It was shown by ab initio calculations that the Heisenberg superexchange is the largest low-energy scale but also Ising-like compass interactions contribute [20]. Therefore, individual Ba 2 IrO 4 layers provide a close realization of the quantum spin-1/2 compass-Heisenberg model [21]. We note that similarly complex structure of the superexchange was established for the honeycomb lattice compound Na 2 TiO 3 , where it takes the form of Kitaev-Heisenberg model which is under intense discussion at present [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case the operators include just one of the orthogonal pseudospin components at each bond and are Ising-like. This form of interactions is found as well in the compass models [28][29][30][31][32][33][34][35][36][37][38][39], and in the Kitaev model on the honeycomb lattice [40][41][42]. The interactions that are considered here are defined by the pseudospin operators T γ i for two active orbitals (for T = 1/2), and we define them as linear combinations of the Pauli matrices {σ These operators define the generalized compass model (GCM) considered in this paper.…”
Section: Introductionmentioning
confidence: 77%
“…For example, the global ground states of the 2D QCM have a ferro-orbital nematic long-range order in a highly degenerate ground state [36,52,53]. It has been shown that this directional long-range order survives in a manifold of low energy excited states when the compass interactions are perturbed by the Heisenberg ones [37] -this property opens its potential application in quantum computation. It is remarkable that the 2D QCM is dual to the toric code model in transverse magnetic field [54] and to the Xu-Moore model (Josephson arrays) [55].…”
Section: Introductionmentioning
confidence: 99%